Estudo teórico do comportamento magnético do composto Y0.8Gd0.2Co3 - Bertagnolli, Cibeli Marzari (2004)
The itinerant ferromagnetic Y Co3, Tc = 301K, presents a crystalline structure with a hexagonal unit cell. It has thirty six atoms that are distributed in five different crystallographic sites, three for the Co and two for Y atoms. In this work we calculate the magnetic moment as a function of temperature to the pseudo-binary compound Y0.8Gd0.2Co3, which has localized and itinerant magnetic behaviour. To determine the localized contribution, which is described by the Brillouin function, is necessary to know the polarization of the d electrons that act at the rare earth sites; the itinerant magnetism is given by the 3d bands of Co atoms. In order to obtain these values we perform a first principle calculation with LMTO method. This calculation show that a little polarization of the Y atoms is contrary to the direction to the magnetization in the Co sites. Adopting the hypothesis that the behaviour of the itinerant electrons is not affected by the dilution of the Gd atoms in the Y Co3 compound, the calculation of the magnetic moment of the localized and itinerant electrons was possible. The temperature effect on the itinerant magnetism was simulated by a function obtained from a rigourous calculation in the functional integral formalism. The pseudobinary total magnetic momentum as a temperature function is obtained by the sum of these two contributions.